Oral microbiome dental caries associated genotypes analysis of 6- to 19-year-old individuals shows novel associations - Vieira, Alexandre R.; Modesto, Adriana (Frontiers in Dental Medicine, 2022)
The need to determine risk factors for complex diseases continues to drive efforts to identify etiological factors of common conditions. Molecular tools have created new opportunities to identify risk factors that may act interactively. The goal of this work was to explore potential interactions between oral microbial species and common genetic variants. Ninety-two 6- to 19-year-old individuals recruited through the University of Pittsburgh Dental Registry and DNA Repository project that had oral microbiome and genotyping of 44 single nucleotide polymorphism (SNP) data available were studied. Over-representation of alleles between individuals with or without particular microorganisms was determined using chi-square or Fisher's exact tests. An alpha of 0.001, to account for multiple testing (0.05/44), was considered statistically significant. Associations were found between Candida albicans and enamelin rs3796704 (p = 0.0006), and Staphylococcus epidermidis and tuftelin rs3828054 (p = 0.001). Microbiota and their metabolites might predispose to oral disease when interacting with the host genetic variation and future studies should address their causal roles in oral disease.